Development-induced Displacement and Human Rights in Africa : the Kampala Convention - Adeola, Romola (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Following independence, many African states embarked on large-scale development projects such as dams, urban renewal and extraction of natural resources and have had to grapple with how to protect displaced communities while implementing development projects. These projects were considered a panacea for Africas development and the economic interests of the majority were often considered over and above the interests of the minority of people who were displaced by these projects. This book examines how a balance can be struck between the imperative of development and the rights of displaced persons the within the context of the African Union Convention on the Protection and Assistance of Internally Displaced Persons in Africa (the Kampala Convention). Romola Adeola analyses the obligations that are placed on African states by the Kampala Convention, shows how institutions beyond the state also have significant roles to in fostering compliance and examines how these actors can be regulated."--Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: African Union Convention for the Protection and Assistance of Internally Displaced Persons -- (2009 October 22); Internally displaced persons -- Legal status, laws, etc. -- Africa; Refugees -- Africa; Forced migration -- Africa; Human rights -- Africa; Law -- Africa; Economic development -- Political aspects; Human rights; Civil rights; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; LAW / International